2006
DOI: 10.4319/lo.2006.51.6.2632
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic control of the underwater light climate in fluvial Lac Saint‐Pierre

Abstract: We measured characteristics of the underwater light spectra (e.g., attenuation of ultraviolet [UV] radiation, photosynthetically active radiation) and select dissolved and particulate physicochemical properties (e.g., chromophoric dissolved organic carbon [CDOM], dissolved and particulate organic carbon, inorganic dry weights, beam attenuation coefficients, particulate absorption coefficients, and nutrients) in different water masses of fluvial Lac Saint-Pierre (Canada). We used these variables as tracers to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…Our study avoids this problem: although treatments without non-selective screens were probably too harsh for larvae, conditions in the other treatments were close to what is potentially found in the field. The irradiance received under the low and medium quantity treatments were close to the light conditions that could be found in the first 30 cm of the water column of some sections of the St. Lawrence River (Frenette et al 2006), where yellow perch larvae are commonly found (Magnan and Bertolo, personal observations). The use of natural solar radiation allowed us to get a more realistic interpretation of the impact of UVR in a natural Our results are in accordance with those of Williamson et al (1997) who showed that yellow perch egg survival was strongly affected when exposed in clear water to UV-B ?…”
Section: Discussionmentioning
confidence: 99%
“…Our study avoids this problem: although treatments without non-selective screens were probably too harsh for larvae, conditions in the other treatments were close to what is potentially found in the field. The irradiance received under the low and medium quantity treatments were close to the light conditions that could be found in the first 30 cm of the water column of some sections of the St. Lawrence River (Frenette et al 2006), where yellow perch larvae are commonly found (Magnan and Bertolo, personal observations). The use of natural solar radiation allowed us to get a more realistic interpretation of the impact of UVR in a natural Our results are in accordance with those of Williamson et al (1997) who showed that yellow perch egg survival was strongly affected when exposed in clear water to UV-B ?…”
Section: Discussionmentioning
confidence: 99%
“…Large, deep rivers can be extreme in this regard. In turbid, well-mixed waters, phytoplankton can be severely light limited, and macrophytes and benthic algae are restricted to the shallowest, light-exposed portions (Frenette et al 2006). At the same time, the flow of water from the watershed brings with it a great deal of dissolved and particulate organic matter of terrestrial origin that can dwarf autochthonous primary production (Vannote et al 1980).…”
mentioning
confidence: 99%
“…Franc ?ois river and the l'Assomption river located, respectively, on the south and north shores, which strongly drain agricultural watersheds. CDOM input in the river from these two tributaries, in particular, and from other tributaries, in general, has already been documented by several authors [e.g., Frenette et al, 2003Frenette et al, , 2006Frenette et al, , 2012Vis et al, 2007;Massicotte and Frenette, 2011].…”
Section: Discussionmentioning
confidence: 90%
“…The SLR forms a complex system composed of a mosaic of heterogeneous zones such as fluvial lakes, connecting reaches and wetlands interacting with inflowing tributaries. In SLR, 21 principal tributaries drain a watershed of 1,600,000 km 2 , where land use is dominated by a high degree of urbanization near Montreal and areas of agriculture, pastures, forests, and wetlands in the mid and lower reaches of the stream system [Frenette et al, 2006, Vis et al, 2007. For instance, water intrusions from tributaries become distinct water masses flowing down the river and contributing to spatial and temporal heterogeneity in optical characteristics [Frenette et al, 2003[Frenette et al, , 2006Rice et al, 2006].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation